Decision Analytic Modeling in Mental Health : Simulating Cost-Effectiveness of Alzheimer's Disease Timely Treatment - Broulíková, Hana Marie, 1989-; Arltová, Markéta, 1970-; Malá, Ivana, 1962-; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2019)
This doctoral thesis concerns the use of decision analytic models for the purposes of economic evaluation in mental-health care. The thesis includes construction of an individual patients’ model examining cost-effectiveness of timely treating Alzheimer’s disease in the Czech Republic. The model is based on a cyclical transition between health states and estimated by the Monte Carlo method.The thesis has three goals. The first one is to assess the possibilities of using nation-wide health care registers to extract the parameters necessary to construct the model. To achieve this goal, an analysis was performed of data concerning patients with Alzheimer’s disease coming from two nation-wide registers: National Register of Hospitalized Patients and of Deaths. The second goal is to analyze the effect of the model’s cycle length on the accuracy of the cost-effectiveness estimate. Especially chronical degenerative illnesses exhibit a conflict between two time-related aspects of the model: The moment of diagnosis can be modelled more accurately with relatively shorter cycles of the model. On the other hand, these illnesses have to be modelled with a long time-horizon. The ensuing computational demandingness calls for relatively longer cycle. Choice between cycle lengths spanning from one month to one year is assessed using a deterministic sensitivity analysis applied to the case study concerning timely treatment of Alzheimer’s disease. The third goal is the actual evaluation of cost-effectiveness shown by the timely treatment of Alzheimer’s disease based on the results of the construed model. This analysis may be used in practice for the purposes of decision-making concerning changes in diagnostic strategies, which belongs among the main priorities of the National Action Plan for Alzheimer’s Disease and Related Illnesses. The analysis of the nation-wide registers indicates that they constitute a valuable source of epidemiological data.
There nevertheless need to be studies on the validity of the recorded entries. The sensitivity analysis of the cycle length shows that the distortion concerning the moment of diagnosis caused by a longer cycle does not lead to substantial difference in the estimation; what is more, the computational demandingness of short cycles is high. Results of the cost-effectiveness analysis support introduction of measures for timely treatment of Alzheimer’s disease.
Vedoucí práce: Markéta Arltová
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: statistika [obor disert. práce]; disertace; dissertations